Mobile Apps as Personal Assistant Agents: the JaCa-Android Framework for programming Agents-based applications on mobile devices - Croatti, Angelo; Ricci, Alessandro (Autonomous agents and multi-agent systems, 2020)
A relevant application domain for agent-based software is given by mobile and wearable applications. In this context, the impressive progress of technologies in the last decade makes it possible to explore the use of agent-oriented programming languages and frameworks based on cognitive architectures, such as the Belief–Desire–Intention (BDI) one. Accordingly, in this paper we provide a comprehensive description of the JaCa-Android approach, a framework based on the JaCaMo platform that allows for designing and programming smart mobile apps using cognitive agents based on the BDI architecture and the Agents & Artifacts environment conceptual model. In these years, the framework has been applied in real-world projects and application domains, and extended and evolved accordingly. The aim of the paper is to report our experience about designing and programming mobile apps as personal assistant agents , as well as to discuss in detail the architecture of the framework.